Montaje y puesta en marcha de la planta piloto de procesamiento de plásticos y laboratorío para análisis y evaluación de plásticos en la ESPOL - Laman A., Pamela (2010)
The plastic industry has been developed of progressive way and therefore the Ecuadorian plastic products must obtain a value added thus this way to be able to compete with plastic industries at world-wide level. But most of the personnel who toils in companies dedicated to the plastic processing does not have a technical formation, their knowledge are very basic therefore they are not very efficient in its jobs. By such reason, in the present project it shows to the assembly and beginning of the production plant and the plastic laboratory of the ESPOL, which includes/understands all the steps necessary to obtain a plant and equipped affluent laboratory in agreement with the present demand, therefore will be able to be analyzed and to be evaluated plastics to improve the competitiveness of the local industries through training, projects of technological innovation, transference of technology, knowledge of the last tendencies.